PCR positivity and D-dimer levels in pregnant women with COVID-19 - K. Uzel; I. Lakhno (IMR Press, 2020)
Background: Every day brings us new data on COVID-19, which has come to affect all the dynamics of the society, and increasingly more scientific literature becomes available on the topic. However, research information about its effects on particular groups, e.g., pregnant women, is still very limited. Aims: This study was aimed to investigate D-dimer levels in pregnant women admitted to the hospital with suspected COVID-19. Study Design: This descriptive cross-sectional study was carried out among pregnant women admitted to our hospital between 1 April 2020 and 31 May 2020 with suspected COVID-19. The data about patients was obtained from patient records and the hospital automation system. Methods: The primary outcome variable of the study was the D-dimer levels. Secondary outcome variables were the presence/absence of cough, shortness of breath, headache, fever, weakness, proteinuria, diarrhoea, haematuria, loss of taste, hypertension, and gestational diabetes mellitus. Results: Data for 64 pregnant women were analyzed. Thirty-three (51.5%) of them had a positive polymerase chain reaction (PCR) results, and thirty-one (48.5%) had negative ones. The mean age of the participants was 26.33 ± 5.15 years. Of the pregnant women, 51.6% (n = 33) were PCR (+) for COVID-19, and 48.5% (n = 31) were PCR (-). The mean age of the participants was 26.33 ± 5.15 years. Headache occurred significantly more often in PCR (+) pregnant women than in PCR (-) ones (χ2 = 4.201, p = 0.040). A statistically significant difference was found when the groups were compared in regard to the presence of the fever symptom (χ2 = 5.036, p = 0.025). When PCR (+) and PCR (-) pregnant women were compared, a statistically significant difference was found in the D-dimer levels (Z = 2.896, p = 0.004). A logistic regression model with PCR positivity as the dependent variables and headache, fever, and D-dimer levels as independent ones revealed a Nagelkerke R2 of 26.8%, and relatively high sensitivity (87.9%) and specificity (59.1%) values in predicting PCR positivity. Conclusion: This research is the first study to have suggested a model for predicting PCR positivity in women suspected of having the COVID-19 disease, which can speed up decision-making in regard to pregnant women with COVID-19.